Microvesicular Caspase-1 Mediates Lymphocyte Apoptosis in Sepsis - Exline, Matthew C. (Public Library of Science, 2014)
OBJECTIVE: Immune dysregulation during sepsis is poorly understood, however, lymphocyte apoptosis has been shown to correlate with poor outcomes in septic patients. The inflammasome, a molecular complex which includes caspase-1, is essential to the innate immune response to infection and also important in sepsis induced apoptosis. Our group has recently demonstrated that endotoxin-stimulated monocytes release microvesicles (MVs) containing caspase-1 that are capable of inducing apoptosis. We sought to determine if MVs containing caspase-1 are being released into the blood during human sepsis and induce apoptosis.. DESIGN: Single-center cohort study MEASUREMENTS: 50 critically ill patients were screened within 24 hours of admission to the intensive care unit and classified as either a septic or a critically ill control. Circulatory MVs were isolated and analyzed for the presence of caspase-1 and the ability to induce lymphocyte apoptosis. Patients remaining in the ICU for 48 hours had repeated measurement of caspase-1 activity on ICU day 3. MAIN RESULTS: Septic patients had higher microvesicular caspase-1 activity 0.05 (0.04, 0.07) AFU versus 0.0 AFU (0, 0.02) (p<0.001) on day 1 and this persisted on day 3, 0.12 (0.1, 0.2) versus 0.02 (0, 0.1) (p<0.001). MVs isolated from septic patients on day 1 were able to induce apoptosis in healthy donor lymphocytes compared with critically ill control patients (17.8±9.2% versus 4.3±2.6% apoptotic cells, p<0.001) and depletion of MVs greatly diminished this apoptotic signal. Inhibition of caspase-1 or the disruption of MV integrity abolished the ability to induce apoptosis. CONCLUSION: These findings suggest that microvesicular caspase-1 is important in the host response to sepsis, at least in part, via its ability to induce lymphocyte apoptosis. The ability of microvesicles to induce apoptosis requires active caspase-1 and intact microvesicles.